The reverse lateral arm fascial flap in interposition arthroplasty for elbow ankylosis - Anyaehie, Udo E.; Eze, Chukwuemeka B.; Eyichukwu, Gabriel O. (International Surgery Journal, 2016)
Interposition arthroplasty for elbow ankylosis is still a practiced surgical procedure in many nations as elbow replacement surgery is yet to be fully established worldwide. For many decades up until today various interposition materials have been used and the jury is still out on the search for the ideal one. We therefore report the surgical technique of the use of the reverse lateral arm fascial flap, which is based on the interosseous recurrent artery, as interposition material following joint release of ankylosed elbow. We recommend that interposition elbow arthroplasty should be done using the reverse lateral arm fascial flap which is easily accessible through the same surgical incision, vascularized and more durable and functional; offers shorter operation time and less donor site morbidity. The use of this material for interposition arthroplasty of the elbow had not been previously reported.